Adsorption of textile dyes from aqueous solutions onto clay: Kinetic modelling and equilibrium isotherm analysis - Açıkyıldız, Metin; Gürses, Ahmet; Güneş, Kübra; Şahin, Elif (Frontiers in Chemistry, 2023)
The commercial activated carbon commonly uses to reduce of dye amount in the textile industry effluents. In this study has focused on the use of a natural clay sample as low cost but potential adsorbent. For this purpose the adsorption of commercial textile dyes, Astrazon Red FBL and Astrazon Blue FGRL, onto clay was investigated. The physicochemical and topographic characteristics of natural clay sample were determined by scanning electron microscopy (SEM), X-Ray fluorescence spectrometry (XRF), X-Ray diffraction (XRD), thermogravimetric analysis (TGA), and cation exchange capacity measurements. It was determined that the major clay mineral was smectite with partial impurities. The effects of several operational parameters such as contact time, initial dye concentration, temperature, and adsorbent dosage on the adsorption process were evaluated. The adsorption kinetics was interpreted with pseudo-first order, pseudo-second order, and intra-particle diffusion models. The equilibrium adsorption data were analyzed using Langmuir, Freundlich, Redlich-Peterson, and Temkin isotherm models. It was determined that the adsorption equilibrium was reached in the first 60 minutes for each dye. The amount of adsorbed dyes onto clay decreased with increasing temperature, similarly, it decreased with increasing sorbent dosage. The kinetic data were well described by pseudo-second order kinetic model, and adsorption equilibrium data was followed both Langmuir and Redlich-Peterson models for each dyes. The adsorption enthalpy and entropy values were calculated as -10.7 kJ.mol-1 and -13.21 J.mol-1.K-1 for astrazon red and those for astrazon blue -11.65 kJ.mol-1 and 37.4 J.mol-1.K-1, respectively. The experimental results support that the physical interactions between clay particles and dye molecules have an important role for the spontaneous adsorption of textile dyes onto the clay. This study revealed that clay could effectively be used as an alternative adsorbent with high removal percentages of astrazon red and astrazon blue.